The Prohibition of Sleeping in Mosques: A Library Research on Islamic Jurisprudence and Contemporary Fatwas - Hajer Abdallah Albshkar; Safa Husayn Alrumayh (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study examines the prohibition of sleeping in mosques through a library research approach, focusing on classical Islamic jurisprudence and contemporary fatwas. The research aims to explore how different schools of Islamic law (madhāhib) conceptualize the permissibility or restriction of sleeping in mosques, and how modern religious authorities interpret and regulate this practice in response to current social contexts. Primary sources such as the Qur’an, Hadith, and classical fiqh manuals are analyzed alongside recent fatwas issued by religious institutions in Indonesia and other Muslim-majority countries. The findings indicate that while sleeping in mosques is generally permitted under certain conditions—such as iʿtikāf, necessity, or travel—many contemporary fatwas and mosque management bodies discourage or restrict the practice to maintain the sanctity, cleanliness, and primary function of the mosque as a place of worship. This study highlights the dynamic interplay between normative Islamic teachings and contemporary socio-institutional needs, revealing ongoing tensions between religious permissibility and practical governance of sacred spaces.